Strategi Islamic Human Capital Management Dalam Peningkatan Kinerja Pegawai Bank Syariah Indonesia - Fatma Devi Dayanti Siagian; Muhammad Lathief Ilhamy Nasution; Muhamad Ikhsan Harahap (Universitas Hamzanwadi, 2023)
Existence of Bank Syariah Indonesia, which is supported by skilled human resources, indicates significant growth in sharia banking. The purpose of this study is to ascertain the degree to which the Islamic human capital management approach enhances the productivity of Bank Syariah Indonesia personnel at KCP Gajah Mada Medan. The authors of this study employed qualitative research techniques, gathering and organizing descriptive data from sources like voice, information, or images that would then be transformed into presentations of descriptive data. The sort of data used in this study was gathered through a variety of data gathering methods, including interviews and documentation. Interactive Milles & Huberman analysis was used for data analysis. The results of this study show that Bank Syariah Indonesia KCP Gajah Mada Medan in implementing an Islamic-based human resource strategy has implemented it in accordance with Sharia theory, when viewed from the employee selection process there is no longer an element of fraud, acts of tyranny and intimidation and training as well as development is very influential to improve employee performance at Bank Syariah Indonesia KCP Gajah Mada Medan